2011
DOI: 10.1002/ijc.25896
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib inhibits receptor phosphorylation and cell growth and enhances antibody‐dependent cellular cytotoxicity of EGFR‐ and HER2‐overexpressing esophageal cancer cell lines

Abstract: Lapatinib is a dual tyrosine kinase inhibitor of the EGFR and HER2 tyrosine kinase domains. EGFR is expressed in 33.3% and HER2 in 30.3% of esophageal squamous cell carcinomas (ESCCs). To explore the potential utility of Lapatinib for therapy of ESCC patients, we evaluated the effect of Lapatinib on a panel of ESCC cell lines. EGFR and HER2 expression by the cell lines was established, and the effects of Lapatinib on inhibition of the phosphorylation of HER2, antiproliferative effect, apoptosisinducing activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…19,20 As expected, Lapatinib upregulated HER2 cell surface expression on both MKN7 and NCI-N87 (Supporting Information Figs. S5A and S5B).…”
Section: Expanded and Activated Nk Cells Showed Anti-her2-mediated Adsupporting
confidence: 69%
“…19,20 As expected, Lapatinib upregulated HER2 cell surface expression on both MKN7 and NCI-N87 (Supporting Information Figs. S5A and S5B).…”
Section: Expanded and Activated Nk Cells Showed Anti-her2-mediated Adsupporting
confidence: 69%
“…VEGFR-2 is activated following stimulation with activation signals, for example binding to its ligand VEGF. A series of cascade reactions downstream of the signal transduction are initiated, enhancing gene transcription in the nucleus and promoting the proliferation and angiogenesis of vascular endothelial cells (8,13,16). Zhang et al (18) reported a xenograft model of human esophageal adenocarcinoma tissue and mouse tumor through application of neoplastic and non-neoplastic Barrett epithelial cells, confirming the aforementioned hypothesis.…”
Section: A B C Dmentioning
confidence: 85%
“…Similarly, VEGFR-2 overexpression is associated with tumor progression, lymph node metastasis and poor prognosis (12,13,16). A total of 119 cases of esophageal carcinoma tissue samples from multi-ethnic patients in Xinjiang were used to evaluate the correlation between the expression of EGFR and VEGFR-2, and the results revealed a significant correlation (P<0.05).…”
Section: A B Cmentioning
confidence: 99%
“…Lapatinib has recently been approved by the U.S. Food and Drug Administration for the treatment of HER2-expressing advanced breast cancer [26], and lapatinib prolonged progression-free survival in patients with HER2-overexpressing advanced or metastatic breast cancer in several clinical trials [25,[27][28][29][30]. Furthermore, we and others showed that lapatinib induces the accumulation of HER2 at the cell surface and enhances the effects of trastuzumab-mediated ADCC in breast cancer and esophageal squamous cell carcinoma [31][32][33].…”
Section: Introductionmentioning
confidence: 90%